Implications and Future Perspectives of AGEs in PCOS Pathophysiology. (March 2019) - Merhi, Zaher; Kandaraki, Eleni A.; Diamanti-Kandarakis, Evanthia
Abstract : Human, animal, and in vitro studies provide evidence that advanced glycation end-products (AGEs) may contribute to the pathogenesis of polycystic ovary syndrome (PCOS) and its metabolic and reproductive consequences. AGEs are able to induce, via activation of key intracellular signaling pathways, the generation of oxidative stress and proinflammatory cytokines, thus contributing to the adverse health impact of PCOS. This review presents the implications of AGEs in several disease pathophysiologies, including PCOS, as well as the cellular and systemic effects of AGEs on insulin resistance (IR), hyperandrogenemia, endoplasmic reticulum (ER) stress, hypoxia, and ovarian function. The gaps in our knowledge will serve as launching pad for future developments ranging from dietary and lifestyle changes to pharmaceutical interventions aiming at potential applications in women with PCOS. Highlights: AGEs are elevated in the serum and the ovarian tissue of women with PCOS, and may contribute to the metabolic and reproductive consequences of PCOS. Studies in vitro and in animal models suggest that AGEs may be associated with abnormal steroidogenesis and folliculogenesis. Women with PCOS have low levels of the anti-inflammatory sRAGE receptors in both the serum and the ovarian follicular fluid. AGEs could alter insulin intracellular signaling and the cellular translocation of glucose transporters, thus leading to tissue IR.